2014
DOI: 10.1111/febs.12817
|View full text |Cite
|
Sign up to set email alerts
|

Cu(II) and dopamine bind to α‐synuclein and cause large conformational changes

Abstract: a-Synuclein (AS) is an intrinsically disordered protein that can misfold and aggregate to form Lewy bodies in dopaminergic neurons, a classic hallmark of Parkinson's disease. The binding of Cu(II) and dopamine to AS was evaluated by nanopore analysis with a-hemolysin. In the absence of Cu(II), wild-type AS (1 lM) readily translocated through the pore with a blockade current of À 85 pA, but mostly bumping events were observed in the presence of 25 lM Cu(II). A binding site in the N-terminus was confirmed, becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 75 publications
(119 reference statements)
2
44
0
Order By: Relevance
“…The values of I and T provide information about the conformation of AS when it is interacting with the pore . When AS is in the unfolded conformation the molecule translocates through the pore, generating a large I and a long T . Conversely, if AS is in a compact conformation, or if it aggregates, it is more likely to bump against the pore, generating a smaller value of I and a shorter T .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of I and T provide information about the conformation of AS when it is interacting with the pore . When AS is in the unfolded conformation the molecule translocates through the pore, generating a large I and a long T . Conversely, if AS is in a compact conformation, or if it aggregates, it is more likely to bump against the pore, generating a smaller value of I and a shorter T .…”
Section: Introductionmentioning
confidence: 99%
“…When AS is in the unfolded conformation the molecule translocates through the pore, generating a large I and a long T . Conversely, if AS is in a compact conformation, or if it aggregates, it is more likely to bump against the pore, generating a smaller value of I and a shorter T . A variety of self‐assembling bacterial pores and solid‐state pores have been investigated but perhaps the most popular of these is the α‐hemolysin toxin derived from Staphylococcus aureus .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al , [150] showed that incubating α-Syn with Cu (II) for 60 h produced protofibrillar, annular and fibrillar species; protofibrils are especially cytotoxic. Interestingly, more α-Syn aggregation was seen in dopaminergic neurons following Cu exposure, suggesting that Cu and dopamine work synergistically on the misfolding and aggregation of α-Syn [56, 127]. …”
Section: Metalsmentioning
confidence: 99%
“…Scarlata and Golebiewska provided a review of the evidence linking a-synuclein aggregation to oxidation and propose a hypothesis that it is the loss of cellular partners under oxidative conditions that promotes aggregation. 70 Buell et al focused on the influence of solution conditions on the nucleation of a-synuclein aggregation. They found that secondary nucleation increases dramatically at pH values below 6, suggesting that some intracellular locations, such as endosomes and lysosomes, may facilitate rapid aggregation.…”
mentioning
confidence: 99%
“…They found that both the binding of dopamine and Cu 2C to a-synuclein caused large conformational changes. 70 Tau is another well-known IDP linked to neurodegeneration. Elbaum-Garfinkle et al used disease-promoting mutants of tau to investigate the link between the microtubule binding of Tau and disease.…”
mentioning
confidence: 99%